1996
DOI: 10.1258/0956462961917843
|View full text |Cite
|
Sign up to set email alerts
|

Systemic strongyloidiasis complicating HIV: a promising response to ivermectin

Abstract: sexually able and well travelled elderly population we should perhaps expect more risk taking behaviour leading to a rise in the number of cases of STDs in mid to late life.Atypical presentations and complications should be expected to occur in these patients and might complicate their management. A sexual history and examination for STDs is appropriate in all elderly patients presenting with urethritis. If any doubt exists as to the aetiology of their symptoms, prompt referral to a department of GUM should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Only four cases were reported from the whole of Africa [43-46], three of which in South Africa, a state where adequate diagnostic facilities are available. We collected 83/244 (34%) reports from North America (USA [47-109] and Canada [110-116]), 58/244 (24%) from Europe (Belgium [40,117], France [118-129], Germany [130,131], Greece [132-134], Italy [135-141], the Netherlands [142-145], Spain [146-155], Switzerland [156], UK [157-164]) and five (2%) from Oceania (Australia [165-168] and New Zealand [169]). In these areas of low/no endemicity, half of the patients were immigrants (70/146, 48%), while a few subjects were veterans (5/146, 3%) who presumably acquired the infection during military service in an endemic country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four cases were reported from the whole of Africa [43-46], three of which in South Africa, a state where adequate diagnostic facilities are available. We collected 83/244 (34%) reports from North America (USA [47-109] and Canada [110-116]), 58/244 (24%) from Europe (Belgium [40,117], France [118-129], Germany [130,131], Greece [132-134], Italy [135-141], the Netherlands [142-145], Spain [146-155], Switzerland [156], UK [157-164]) and five (2%) from Oceania (Australia [165-168] and New Zealand [169]). In these areas of low/no endemicity, half of the patients were immigrants (70/146, 48%), while a few subjects were veterans (5/146, 3%) who presumably acquired the infection during military service in an endemic country.…”
Section: Resultsmentioning
confidence: 99%
“…In a couple of organ transplant recipients, an ELISA test was negative pre-transplant, but resulted positive in the deceased donors (test performed retrospectively) [60,145]. In other two cases serology (ELISA) was negative: a HIV-infected person, who had larvae in stool and sputum [165] and a patient with dermatomyositis, under chronic treatment with prednisone and methotrexate, who died from disseminated strongyloidiasis (larvae found at autopsy in skin, lungs, small and large bowel, gall bladder, vessels of meninges and cervical spinal cord) [100]. …”
Section: Resultsmentioning
confidence: 99%
“…8,9 Because the number of cases is few, however, the effectiveness of ivermectin against strongyloidiasis in patients infected with HIV has not been fully studied. The disappearance of S. stercoralis and its symptoms after the administration of ivermectin in our patient may indicate that strongylodiasis is a curable disease, even in patients with AIDS, and at the same dose as for patients infected with S. stercoralis without HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted delays in HIV disease progression following deworming (Brown 2005; Ivan 2015; Lankowski 2014; Mulu 2013; Muok 2013; Wolday 2002 ), while others have reported no association (Brown 2004; Elliott 2003; Hosseinipour 2007; Kleppa 2014; Lawn 2000; Modjarrad 2005). In the previous version of this systematic review we found some evidence from randomized controlled trials of short term benefits with deworming but also the need for further larger studies (Walson 2009).…”
Section: Introductionmentioning
confidence: 99%